Basic Concepts and school performance in girls at first grade and low SES - La Rosa Cormack, María Isabel (1995)
The finality of this work was to solve the question about the relationship between knowledge of basic concepts such as: space, time quantity and number, and school performance. The sample was conformed by 30 low school first grade students aged 6 years belonging to low SES. The Boehm Test of Basic Concepts and a Pedagogical Test were administred to asses performance in language and mathematics. Significant correlation was founded between the study variables being higher the relation about concepts and language than concepts and mathematics.